Rv2577 of Mycobacterium tuberculosis Is a Virulence Factor With Dual Phosphatase and Phosphodiesterase Functions - Forrellad, Marina Andrea; Blanco, Federico Carlos; Marrero Diaz de Villegas, Rubén; Vázquez, Cristina Lourdes; Yaneff, Agustín; García, Elizabeth Andrea; Gutierrez, Maximiliano Gabriel; Durán, Rosario; Villarino, Andrea; Bigi, Fabiana (Frontiers in Microbiology, 2020)
Tuberculosis, a lung disease caused by Mycobacterium tuberculosis (Mtb), is one of the ten leading causes of death worldwide affecting mainly developing countries. Mtb can persist and survive inside of infected cells through modulation of host antibacterial attack, i.e. avoiding the maturation of phagosome containing mycobacteria to more acidic endosomal compartment. In this interplay between host cell and Mtb, bacterial phosphatases play a central role. In this work, we characterized the Rv2577 of Mtb as a potential alkaline phosphatase/phosphodiesterase enzyme. By an in vitro kinetic study, we demonstrated that purified Rv2577 expressed in Mycobacterium smegmatis displays both enzyme activities, as evidenced by using the artificial substrates p-NPP and bis-(p-NPP). In addition, a three-dimensional model of Rv2577 allowed us to define the catalytic amino acid residues of the active site, which were confirmed by site-directed mutagenesis and enzyme activity analysis. Finally, mutation of Rv2577 reduced the replication of Mtb in mouse organs and impaired the arrest of phagosome containing mycobacteria in early endosome, indicating that Rv2577 plays a role in the virulence of Mtb.